Choline Inadequacy Impairs Trophoblast Function and Vascularization in Cultured Human Placental Trophoblasts. Issue 8 (August 2014) - Jiang, Xinyin; Jones, Sara; Andrew, Benjamin Y.; Ganti, Anita; Malysheva, Olga V.; Giallourou, Natasa; Brannon, Patsy M.; Roberson, Mark S.; Caudill, Marie A.
<x xml:space="preserve">Abstract</x> Maternal choline intake during gestation may influence placental function and fetal health outcomes. Specifically, we previously showed that supplemental choline reduced placental and maternal circulating concentrations of the anti‐angiogenic factor, fms‐like tyrosine kinase‐1 (sFLT1), in pregnant women as well as sFLT1 production in cultured human trophoblasts. The current study aimed to quantify the effect of choline on a wider array of biomarkers related to trophoblast function and to elucidate possible mechanisms. Immortalized HTR‐8/SVneo trophoblasts were cultured in different choline concentrations (8, 13, and 28 µM [control]) for 96‐h and markers of angiogenesis, inflammation, apoptosis, and blood vessel formation were examined. Choline insufficiency altered the angiogenic profile, impaired in vitro angiogenesis, increased inflammation, induced apoptosis, increased oxidative stress, and yielded greater levels of protein kinase C (PKC) isoforms δ and ϵ possibly through increases in the PKC activators 1‐stearoyl‐2‐arachidonoyl‐sn‐glycerol and 1‐stearoyl‐2‐docosahexaenoyl‐sn‐glycerol. Notably, the addition of a PKC inhibitor normalized angiogenesis and apoptosis, and partially rescued the aberrant gene expression profile. Together these results suggest that choline inadequacy may contribute to placental dysfunction and the development of disorders related to placental insufficiency by activating PKC. J. Cell. Physiol. 229: 1016–1027, 2014. © 2013 Wiley Periodicals, Inc.